Histamine H1 receptor antagonist attenuates catecholamine surge and organ injury after severe burns - Wang, Jizhuang; Lu, Chenghao; Liu, Xinying; Zhang, Gai; Zhang, Jie; Gao, Min; Liu, Dan; Zhang, Xiong; Liu, Yan (Frontiers in Endocrinology, 2023)
Severe burns induce a catecholamine surge, causing severe damage to the organism and raising the possibility of multisystem organ failure. Few strategies are generally acceptable to reduce catecholamine surge and organ injury post-burn. We have previously shown that histamine can amplify the catecholamine surge. In addition, promethazine, a first-generation histamine H1 receptor antagonist, alleviates catecholamine surge and organ injury after severe burns in rats. However, evidence is lacking on whether promethazine benefits patients after severe burns. Currently, sedation and analgesia (such as midazolam and fentanyl) are commonly required for patients after severe burns. It remains unclear if patients after severe burns derive clinical benefit from histamine H1 receptor antagonists combined with sedation and analgesia. This study investigates the therapeutic effect of promethazine on patients after severe burns. Moreover, we test the therapeutic effect of cetirizine, a second-generation histamine H1 receptor antagonist, combined with sedation and analgesia in rats after severe burns. We find that promethazine-pethidine treatment shows a tendency for a lower level of total bilirubin than midazolam-fentanyl in patients 7-day after severe burn. Our study confirms that cetirizine combined with midazolam and fentanyl reduces catecholamine surge and liver and lung damage after severe burns in rats; the effects are better than midazolam and fentanyl treatment. In summary, for the first time, we suggest that histamine H1 receptor antagonist has the potential clinical value of reducing liver injury in patients after severe burns. In addition, we reveal that cetirizine combined with midazolam and fentanyl may be an ideal strategy for treating severe burns.